Understanding the bug that make our drugs: Cellular responses to therapeutic protein secretion in E. coli. Issue 5 (27th May 2022) - Seleiro, Alice; Evans, Caroline; Green, Jeff; Lennon, Chris; Stafford, Graham
Abstract : Production of therapeutic proteins is a $200 billion industry with E. coli being one of the main expression systems used and proteins often being secreted to the periplasm to produce disulphide bonds. However, little is known about how E. coliresponds to secretion of these therapeutic proteins into the periplasm under industrial conditions. Proteomics and transcriptomics were conducted on cultures grown at high cell density in industrial production conditions to look at the effect of secreting a model therapeutic protein (scFv) to the periplasm compared to expressing the same protein in the cytoplasm. 82 proteins and 1653 transcripts were differentially expressed when overexpressing the scFv in different cellular compartments. ScFv secretion had a significant effect on expression of genes involved in the envelope stress response. However, while certain envelope stress pathways where upregulated upon secretion others were downregulated (including expression of some periplasmic chaperones). Scfv secretion also led to an increase in expression of genes involved in degradation of membrane proteins and the SEC secretion system, as well as iron transport, Outer membrane porins and flagella operons. In future and current experiments, we are testing whether knocking out and overexpressing a selection of these genes improves secretion and folding of scFvs and other recombinant proteins.